Verification as Learning Geometric Concepts - and Gupta, Saurabh; Hariharan, Bharath; Aiken, Alex; Nori, Aditya (Static Analysis Symposium (SAS), 2013)
We formalize the problem of program verification as a learning problem, showing that invariants in program verification can be regarded as geometric concepts in machine learning. Safety properties define bad states: states a program should not reach. Program verification explains why a program's set of reachable states is disjoint from the set of bad states. In Hoare Logic, these explanations are predicates that form inductive assertions. Using samples for reachable and bad states and by applying well known machine learning algorithms for classification, we are able to generate inductive assertions. By relaxing the search for an exact proof to classifiers, we obtain complexity theoretic improvements. Further, we extend the learning algorithm to obtain a sound procedure that can generate proofs containing invariants that are arbitrary Boolean combinations of polynomial inequalities. We have evaluated our approach on a number of challenging benchmarks and the results are promising.